Strategi Pencegahan Korupsi melalui Penerapan Sistem Manajemen Anti Penyuapan (SMAP) ISO 37001:2016 - Widodo Teguh Santoso; Fadlan Suryadi (Sekolah Pascasarjana Perbanas Jakarta, 2022)
Corruption cases, especially bribery cases, still occur in the government sector. Prevention efforts are strategic things to be implemented. One of the strategies to prevent bribery in the government sector is to implement the Anti-Bribery Management System (SMAP) ISO 37001: 2016. This study aims to analyze the extent to which the implementations of SMAP ISO 37001:2016 in government working units in preventing corruption. The case study was conducted in 2 (two) working unit in Agricultural Quarantine Center, Indonesian Ministry of Agriculture, namely Satker X and Y. The research was conducted by interview method using questionnaire to the Compliance Unit and the employee who provided the public services. This study uses a quantitative approach with data analysis methods referring to univariate data analysis using descriptive statistics. The data used in this study is primary data in the form of questionnaire containing 62 questions grouped into 7 (seven) aspects which are aspects that must be met according to ISO 37001:2016, namely: Organizational Institutional Aspects, Leadership Aspects, Planning Aspects, Aspects Support, Operations Aspect, Management Review Aspect, and Improvement Aspect. The results of the research on the 2 (two) working units, shows that all aspects of the requirements have been met according to SMAP. In Satker X, it has a value between 97.12% to 99.36% or is at a level that is mostly fulfilled. Meanwhile, Satker Y has a value between 95.00% to 98.75% or is at a level that is mostly fulfilled. Suggestions are given to the work unit in order to maintain and be obliged continuously and continuously to improve the quality of public services related to the implementation of this SMAP in the organization